PEMBERIAN PROGESTERON PADA KEGUGURAN BERULANG - Suparman, Erna; Suparman, Eddy (UNIVERSITAS SAM RATULANGI, 2013)
Abstract: Recurrent pregnancy loss (RPL) occurs in 0.5-1% of partners. The pathophysiology of this RPL is complex. The causes include anatomical, genetic and molecular abnormalities, endocrine disorders, thrombophilia, and the anti-phospholipid syndrome, meanwhile in 50% of cases no cause can be identified. Progesterone is needed to create a suitable environment for the implantation. Low progesterone level during early pregnancy may reflect corpus luteum defects or abnormal products of conception. Besides that, low progesterone is a sign of a coming miscarriage; an administration of progesterone can only delay the onset of bleeding.. Even with a normal plasma progesterone levels, endometrial progesterone deficiency can still result from receptor defects; this finding supports the existence of absolute or relative progessterone deficiency as a cause of spontaneous abortion. Women who suffer from relative progesterone deficiency probably will not get any benefit from progesterone therapy. Almost all current research states that there is no difference in the rates of miscarriages in women treated and not treated with progesterone. Therefore, all medical organizations do not recommend progesterone supplementation to recurrent miscarriage, except in women who use reproductive technologies such as in vitro fertilization (IVF). Keywords: recurrent pregnancy loss, progesterone. Â Â Abstrak: Keguguran berulang terjadi pada 0,5-1% pasangan dengan patofisiologi yang kompleks. Sebagai penyebab ialah kelainan anatomi, genetik dan molekuler, gangguan endokrin, thrombofilia, dan sindrom anti-fosfolipid, tetapi pada 50% kasus tidak jelas. Progesteron sangat diperlukan dalam menciptakan lingkungan yang cocok untuk implantasi endometrium. Konsentrasi progesteron yang rendah selama awal kehamilan mencerminkan defek korpus luteum atau hasil konsepsi yang abnormal. Progesteron yang rendah merupakan tanda dari keguguran akan datang namun pemberian progesteron hanya dapat menunda timbulnya perdarahan. Walaupun tingkat progesteron plasma normal, endometrium masih dapat mengalami kekurangan progesteron akibat defek reseptor. Temuan ini mendukung adanya defisiensi progesteron absolut atau relatif sebagai penyebab keguguran spontan. Wanita yang menderita kekurangan progesteron relatif tidak akan mendapatkan keuntungan dari pemberian progesteron. Hampir semua penelitian saat ini menyatakan bahwa tidak terdapat perbedaan tingkat keguguran pada wanita yang diberikan progesteron dan yang tidak; oleh karena itu semua organisasi medis tidak menganjurkan pemberian progesteron pada keguguran berulang, kecuali pada wanita yang menggunakan teknologi reproduksi seperti IVF. Kata kunci: keguguran berulang, progesteron.